The Use of Chain Blocks in the Maintenance of Intellectual Property Rights - Alsefri, Abdullah ALHassan (Journal of Economic, Administrative and Legal Sciences, 2020)
The present study aimed to identify the reality of the use of blocks series in the process of preserving intellectual property rights, and the study adopted the theoretical documentary approach, and the study relied on books, documents, reports and studies published Internet sites in the 'list, and was addressed to the general framework of the study deals with the introduction, problem and importance To the theoretical side of the study in which the researcher addressed a literary review of more than one aspect of the issue of the series of blocks and intellectual property rights, the researcher concluded at the end of the research to a set of results, the most important of which while the technology of the blockchain can bring innovation in many sectors Despite the enthusiasm for this technology, it should not be considered a "magic bullet." Instead, it should be carefully evaluated according to the objectives of the company sector and its business. The use of electronic systems for a long time, such as banks, insurance companies, etc. There is a difficulty in getting rid of their systems and replace them with a new system do not know the risks of its application and there are no uniform standards.
Keywords: block chain; copyright; intellectual property; intellectual property rights